Subsídios agrícolas, suporte e políticas comerciais nos grandes importadores de alimentos: UE, China, Estados Unidos e Jap\~ao - Rogério Edivaldo Freitas (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The goal was to analyze the trend of agricultural support in the European Union (EU), China, the United States of America (USA), and Japan from 2000 to 2022. Producer Support Estimate (PSE) and Consumer Support Estimate (CSE) estimates organized by the Organization for Economic Cooperation and Development (OECD) were evaluated and a qualitative analysis was equally performed. Results point out that agricultural support in the EU, USA, and Japan is decreasing in the producer activities while it is also becoming more intense on the consumer side. In contrast, the Chinese case exposed the inverse processes. In the qualitative evaluation, it was possible to map the profile of agricultural support and protection strategically designed in the four big markets, which includes border measures, domestic support programs, and an intense effort to consolidate bilateral agreements comprising food products; this last one especially in the USA and Chinese initiatives. The four big markets also practice several actions to reinforce agricultural insurance tools and research investments targeted to the present environmental restrictions. For Brazilian interests, the main message is to monitor those partners in their (big four) supply-demand conditions for agricultural goods and their domestic and trade policies affecting such products. At the same time, initiatives to address sanitary issues and technical barriers related to Brazilian food products are also welcome.
Keywords: Q17; Q18; 330; agricultural trade; OECD; agricultural support; agricultural policies